DIABETIC RETINOPATHY AND ITS INTERPRETATIONS THROUGH AYURVED (AYUSHDHARA, 2019)
Chaksyu is the Pradhana-anga that is affected in Diabetic retinopathy. So the Netra Rakshana is highly essential for the human being in Diabetic retinopathy. Now-a-Days Diabetic retinopathy is a major vision threatening factor. The prevalence rates are; Diabetic retinopathy (34.6%), Proliferative Diabetic retinopathy (7%), diabetic macular oedema (6.8%) and Vision threatening Diabetic retinopathy (10.2%). To treat the disease we need to know the level of impairment, the signs and its etiopathology. In Ayurved it is very important to know the Samprapti before treating the disease. Now-a-days Pratyaksha gyana plays a vital role to trace out the disease. Complain of the patient, sign and symptom of the disease along with the pathogenesis is necessary to diagnose and to treat the disease. The features occurs in the fundus in Diabetic retinopathy cannot visualize by Pratyaksha, explained in classical literatures. Many ophthalmic investigations, procedures have been developed so far like fundoscopy, OCT, B’scan, fluorescent test etc. to detect the pathology occurred in the fundus of Diabetic retinopathy eyes. So it is very important for all Shalaki is to correlate the disease, to derive a conclusion according to the Ayurvedic Samprapti/ pathogenesis and terminology described in classical literatures. By analyzing the Samprapti of the disease we can conclude that, the pathology occurred in fundus are most probably due to the Dhatu-kshaya janya, Urdhwaga-raktapittaja, Mandagni janya and Avarana janya. Diabetic retinopathy can be correlated with Pramehaja Timira and its treatment is the treatment of Prameha explained in classics having Chakshushya property.